A meta‐analysis and cost‐minimization analysis of bivalirudin versus heparin in high‐risk patients for percutaneous coronary intervention. Issue 3 (3rd May 2021) - Sun, Ke‐Xin; Cui, Bin; Cao, Shan‐Shan; Wang, Wen‐Jun; Yu, Feng; Wang, Jing‐Wen; Ding, Yi
Abstract: This meta‐analysis was performed to compare the safety, efficacy, and pharmacoeconomic of bivalirudin versus heparin in high‐risk patients for percutaneous coronary interventions (PCI). Earlier meta‐analysis comparing bivalirudin and heparin during PCI demonstrated that bivalirudin caused less bleeding with more stent thrombosis. However, little data were available on the safety of bivalirudin versus heparin in high‐risk patients for PCI. Thus, we performed a meta‐analysis to evaluate the efficacy and safety in the "high‐risk" patients. A systematic search of electronic databases was conducted up to July 30, 2020. The Cochrane Risk of Bias assessment tool was used to assess the quality of included studies. The primary outcomes were all‐cause death and major adverse cardiac events (MACE); secondary outcomes were major and minor bleeding, followed by a cost‐minimization analysis comparing bivalirudin and heparin using a local drug and medical costs reported in China. Subgroup analysis was based on the type of disease of the high‐risk population. Finally, a total of 10 randomized controlled trials involved 42, 699 patients were collected. The Cochrane Risk of Bias Tool was employed to appraise the research quality. No significant difference was noted between bivalirudin and heparin regarding all‐cause death and MACE. However, subgroup analysis showed that bivalirudin caused less major bleeding in female (OR:0.65, 95% CI:0.53–0.79), diabetes (OR:0.55, 95%CI:0.42–0.73), and CKD (OR:0.59, 95%CI:0.63–1.65). The scatterers of the included literature were approximately symmetrical, and no research was outside the funnel plot. Additionally, cost‐minimization analysis showed that heparin was likely to represent a cost‐effective option compared with bivalirudin in China, with potential savings of 2129.53 Chinese Yuan (CNY) per patient for one PCI. Overall, the meta‐analysis showed that although bivalirudin appeared to have a lower risk of major bleeding rate, the overall effectiveness and safety between the two groups showed no significant difference in high‐risk patients for PCI. But the results of the cost‐minimization analysis showed that heparin could be a potential cost‐saving drug than bivalirudin in patients for PCI in China. Abstract : This meta‐analysis showed that although bivalirudin appeared to have a lower risk of major bleeding rate, the overall effectiveness and safety between the two groups showed no significant difference in high‐risk patients for PCI. But the results of the cost‐minimization analysis showed that heparin could be a potential cost‐saving drug than bivalirudin in patients for PCI in China. ​